2015
DOI: 10.1163/18781527-00601005
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Human Rights and Disaster Risk Reduction Revisited: Bringing the Legal Perspective into the Discussion

Abstract: This paper explores the link between human rights and disaster risk reduction. We revisit the notion of a human rights-based approach in the context of natural disasters, analyzing how this concept may contribute to greater accountability and empowerment of those involved in disaster risk reduction. To better understand the processes of empowering rights holders and holding duty bearers into account we adopt legal analytical lenses. By doing so we review four country case studies and their main regulations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
8
0
9
Order By: Relevance
“…Turning to vulnerabilities and capacities, international human rights law is particularly relevant. Significant discussion has centered on a human rights-based approach to DRR, and the Sendai Framework highlights the importance of human rights in paragraph 19(c) (Enarson and Fordham 2001;Cubie 2014;da Costa and Pospieszna 2015;Lauta 2015Lauta , 2016Aronsson-Storrier 2017;Sossai et al 2018;Hesselman et al 2019). A human rights-based approach to DRR certainly has its merits.…”
Section: Turning the Wheel? Regulating Disaster Risk Reductionmentioning
confidence: 99%
“…Turning to vulnerabilities and capacities, international human rights law is particularly relevant. Significant discussion has centered on a human rights-based approach to DRR, and the Sendai Framework highlights the importance of human rights in paragraph 19(c) (Enarson and Fordham 2001;Cubie 2014;da Costa and Pospieszna 2015;Lauta 2015Lauta , 2016Aronsson-Storrier 2017;Sossai et al 2018;Hesselman et al 2019). A human rights-based approach to DRR certainly has its merits.…”
Section: Turning the Wheel? Regulating Disaster Risk Reductionmentioning
confidence: 99%
“…Providing shelter is not charity, compassion or favor: it is a universal right. When a disaster takes place and relief is provided, governments can be held accountable (Da Costa and Pospieszna 2015).…”
Section: Human Right Framework For Disastersmentioning
confidence: 99%
“…The reader will notice that all four contributions in the current special column relate to international human rights law. Although we will introduce each article in due course, the general explanation for this is simple: human rights are indeed an area of international law that has steadily developed in the last few decades, and while the relationship between human rights and disasters has lately received significant attention, from both legal practitioners and academics alike (Kälin and Dale, 2008;Carmalt and Dale, 2012;Sommario, 2012;Cubie and Hesselman, 2015;Da Costa and Pospieszna, 2015), it is clear that the issue warrants deeper and more extensive analysis. Considering the move from a needs-based to a human rights-based approach to disaster management, some have suggested that the protection from human rights violations in disasters is as important as the provision of relief.…”
Section: Disasters and International Human Rights Lawmentioning
confidence: 99%